Riau Petanque Athlete Profile Judging from the Effectiveness of Time in Shooting - M. Fransazeli Makorohim; Alficandra Alficandra; Sasmarianto Sasmarianto (JUARA : Jurnal Olahraga, 2022)
This study reviews the description of the Riau province's petanque athletes in shooting in terms of time effectiveness. This study aims to determine what factors can affect the effectiveness of time in shooting in the petanque sport. The subjects of this research are several related stakeholders (athletes, coaches, and arbitrators) of Riau province. The research method used is the descriptive method. Data collection techniques include observation, interviews, documentation, and data triangulation. The data obtained were analyzed qualitatively by 1) data reduction, 2) data presentation, and 3) drawing conclusions. Based on the results of the study, it was found that the average petanque athlete in Riau Province 1) was still in a hurry to shoot, 2) was inconsistent about the target, 3) lacked focus, 4) was nervous or lacked confidence in the circle, 5) the shooting rate was low. Not maximal. It can be concluded that the effectiveness of time in shooting is significant and affects the shooting results of Riau petanque athletes.